(untitled) (Chemical Engineering Research Bulletin, 2015)
Gas holdup in the column section of bubble columns is determined by a large number of operating-design variables-parameters. In this study the effect of orifice inclination on the gas holdup is investigated at various superficial gas velocities. It is observed that the effect depends largely on the gas velocities. At very low gas velocities such as 0.015-0.076 cm/s where truly dispersed-bubble regime prevails, an inclination of the orifice keeping the size unchanged tends to decrease the gas holdup. However this effect diminishes with increasing gas velocity and no remarkable effect is found at relatively higher gas velocities like 2.20-8.50 cm/s where dispersed-transition-coalesced bubble regimes prevail. Therefore when bubble columns are intended to operate at very low superficial gas velocities, the orifice inclination is also an alternative option to control the gas holdup at the desired level. The experimental results produced in this study would be useful for the development and validation of proper mathematical model. DOI: http://dx.doi.org/10.3329/cerb.v17i1.22914 Chemical Engineering Research Bulletin 17(2015) 18-24